Modern Family Institution: A study on Gender Representations in Malaysian Advertisement - Md Isa, Noor Shamsarini; Hairul Anuar, Inda Murni; Sayed Mothar, Syaripah Mohaizah (Research in Management of Technology and Business, 2024)
Modern family institutions in Malaysia differ significantly from pre-modern times. This article will examine the concept of “family” by tracing its origin and analyzing what constitutes a “family” in Malaysian society. The authors argue that Western modernity's ideas on understanding the concept of family influenced how Malay directed its outlook on their advertisement. The study argues that a patriarchal order exists in Malay society and Connell’s theory of gender and power serve as a framework in analyzing the traits. Of all advertisements analyzed, there are certain significant traits exhibit such as equality in the occupational segregation and cooperation between men and women in childcare duties which weaken the “hegemonic masculinity” as suggested by Connell. However, there are the traits of patriarchal order in the society particularly in the domestic responsibilities which need to be address since it creates imbalance division of labor in a household between two genders.